2014
DOI: 10.1210/jc.2014-1901
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perchlorate Levels in Women With Borderline Thyroid Function During Pregnancy and the Cognitive Development of Their Offspring: Data From the Controlled Antenatal Thyroid Study

Abstract: This is the first study using individual-level patient data to study maternal perchlorate exposure and offspring neurodevelopment and suggests that high-end maternal perchlorate levels in hypothyroid/hypothyroxinemic pregnant women have an adverse effect on offspring cognitive development, not affected by maternal levothyroxine therapy. These results require replication in additional studies, including in the euthyroid population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 34 publications
1
48
2
1
Order By: Relevance
“…In a large cohort of hypothyroid/hypothyroxinemic pregnant women in the multicentre Controlled Antenatal Thyroid Screening Study (CATS), a retrospective analysis aimed at evaluating the impact of maternal perchlorate in the first trimester of pregnancy, demonstrated a significant association with reduced Intelligence Quotient in the offsprings. It is worth noticing that the Intelligence Quotient was in the lower 10 percentile in the offspring of mothers with the highest perchlorate levels [25].…”
Section: Industrial Chemicalsmentioning
confidence: 99%
“…In a large cohort of hypothyroid/hypothyroxinemic pregnant women in the multicentre Controlled Antenatal Thyroid Screening Study (CATS), a retrospective analysis aimed at evaluating the impact of maternal perchlorate in the first trimester of pregnancy, demonstrated a significant association with reduced Intelligence Quotient in the offsprings. It is worth noticing that the Intelligence Quotient was in the lower 10 percentile in the offspring of mothers with the highest perchlorate levels [25].…”
Section: Industrial Chemicalsmentioning
confidence: 99%
“…However, it is also possible that the model overpredicts the effects of low-dose perchlorate exposures due to it being calibrated with the data from T茅llez-T茅llez et al (2005), which did not take into account possible co-exposures to other goitrogens in the Chilean populations. This concern is acknowledged in Taylor et al (2014), when the authors state as one of the limitations of their study (which found fetal effects in iodine deficient women), "鈥t is equally possible that perchlorate exposure is a surrogate marker for other environmental contaminants or for a combination of multiple other factors which act as disruptors of the fetal/neo-natal thyroid." As with much of the data generated for understanding the risks of perchlorate exposure, considerable uncertainty remains; either the model is overpredicting effects, or it is accurate and the Braverman et al study simply did not have the power to detect such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Urine perchlorate was identified in all women (mean 2.58 碌g/L). It is worth noticing that the Intelligence Quotient was in the lower 10th percentile in the offspring of mothers with the highest perchlorate levels [28].…”
Section: Perchloratementioning
confidence: 99%